New and previously described Acleotrema species (Monogenea, Diplectanidae) parasitizing sea chubs (Centrarchiformes: Kyphosidae) in the Southeastern Pacific Ocean - Santillan, Angel L.; Cruces, Celso L.; Mondragón-Martínez, Aarón; Rojas, Rosa Martínez-; Chero, Jhon D. (Zootaxa, 2025)
During a study on the diversity of monogeneans infecting kyphosid fishes off the coast of Puerto Santa Rosa, Lambayeque region, northern Peru, specimens of the Cortez sea chub Kyphosus elegans (Peters) and the brassy chub K. vaigiensis (Quoy & Gaimard) were examined. Five diplectanids, including a new species, were identified: Acleotrema alejandroi sp. nov. from K. vaigiensis; A. diplobulbus (Yamaguti, 1968) from K. vaigiensis; A. nenue (Yamaguti, 1968) Dominques & Boeger, 2007 from both K. vaigiensis and K. elegans; A. oliveri (León-Régagnon, Pérez-Ponce de León & Garcia Prieto, 1997) from K. elegans and K. vaigiensis; A. spiculare (Yamaguti, 1968) from K. vaigiensis. Acleotrema alejandroi sp. nov. is easily differentiated from all congeneric species by its male copulatory organ (MCO), which is J-shaped with a spatulate distal end. The middle portion of MCO is surrounded by a sclerotized sac; and the distal portion of the sac bears an elongated, sclerotized U-shaped process. Acleotrema oliveri is redescribed based on examination of the type specimen (holotype and paratypes) and newly collected specimens. In addition, new morphometric data and whole-mount drawing of A. nenue, A. spiculare and A. diplobulbus are provided. Acleotrema nenuoides (Rakotofiringa, Oliver & Lambert, 1987) is considered a junior synonym of A. nenue. The present finding brings to 13, the number of known species of Acleotrema Johnston & Tiegs, 1922, and represents the first diplectanid species infecting kyphosid fishes from Peru. Furthermore, this study represents the first record of A. spiculare and A. diplobulbus after more than 50 years.